PSII-B-22 High-impact minimester course in animal science. (8th October 2021) - Bowhay, Ciana; Wickersham, Tryon; Dunlap, Kathrin
Abstract: Many Animal Science students have little exposure to working livestock production systems prior to entering college. As such, they can lack insight into day-to-day challenges and rationale behind decision making in these systems, opening the door for adoption of misconceptions frequently promoted in popular press. Additionally, students identify lack of first-hand knowledge and experience in the industry as a challenge to their educational success. Field trips stimulate interest and motivation, provide context for learning, and influence long-term career goals, but are underutilized in higher education. Potential impact of such experiences prompted creation of the Texas Panhandle Beef Production Tour, a 2-credit hour course that takes place during the spring minimester. To cement learning through reflection, students were asked to respond to a series of questions before, during, and after visiting beef production sites in the Texas Panhandle to probe preconceptions, observations, and outcomes of the experience. We then performed a retroactive evaluation of these reflections (n = 22) to determine cogent themes. Emergent themes included surprise at the intensive systems of data collection and management and the level of technology used at each site. Cattle were calmer and more comfortable than expected at feedlots, dairy, and packing plants visited. Students expressed new appreciation and understanding of course material and a desire to share their insights with others after completing the tour. Finally, participants gained a broader view of industry opportunities and returned with renewed motivation to pursue additional hands-on opportunities. Participation in this course provided valuable insight into the livestock production industry and motivated students to explore new career options and address their own preconceptions of the industry through independent inquiry. Creation of similar courses may be useful to address misconceptions, create personal connections with course material, and broaden career interests in undergraduate animal science students.